2016
DOI: 10.1158/1078-0432.ccr-15-0964
|View full text |Cite
|
Sign up to set email alerts
|

Using Whole-Exome Sequencing to Identify Genetic Markers for Carboplatin and Gemcitabine-Induced Toxicities

Abstract: Purpose: Chemotherapies are associated with significant interindividual variability in therapeutic effect and adverse drug reactions. In lung cancer, the use of gemcitabine and carboplatin induces grade 3 or 4 myelosuppression in about a quarter of the patients, while an equal fraction of patients is basically unaffected in terms of myelosuppressive side effects. We therefore set out to identify genetic markers for gemcitabine/carboplatin-induced myelosuppression.Experimental Design: We exome sequenced 32 pati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 33 publications
0
27
0
2
Order By: Relevance
“…Even if the cohort was small, the results were consistent showing the same trend in most patients and, hence, small variations. Myelosuppression is a well-known side effect of chemotherapies [ 20 ]. Thus, also we observed that myeloid cells including MDSCs were reduced by gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the cohort was small, the results were consistent showing the same trend in most patients and, hence, small variations. Myelosuppression is a well-known side effect of chemotherapies [ 20 ]. Thus, also we observed that myeloid cells including MDSCs were reduced by gemcitabine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the dichotomized classification by the occurrence of grade 3–4 myelosuppression in previous studies, the GWAS used ordinal logistic regression to analyze the association of the myelosuppression grade with SNPs. Another study used whole‐exome sequencing to identify genetic markers for grade 3–4 neutropenia and thrombocytopenia in gemcitabine/carboplatin chemotherapy . The two studies identified several genetic markers related with myelosuppression risk, but there is a lack of functional studies and the results have not be analyzed or replicated in other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, determining the association between polymorphisms and platinum-related toxicities will be beneficial for individualized chemotherapy. Previously, two genome-wide association studies and one wholeexome sequencing study were conducted to identify the genetic markers for platinum-induced toxicities (9)(10)(11). In addition, Yin et al aimed to establish models to explain and predict platinum toxicity interindividual difference by simultaneously incorporating multiple genetic and clinical factors to explore the association of their interactions with platinum-induced toxicities (12,13).…”
Section: Introductionmentioning
confidence: 99%